The Impact of Single Nucleotide Polymorphism in the Long Non-coding MEG3 Gene on MicroRNA-182 and MicroRNA-29 Expression Levels in the Development of Breast Cancer in Egyptian Women - Shaker, Olfat; Ayeldeen, Ghada; Abdelhamid, Amr (Frontiers in Genetics, 2021)
Early-stage detection of BC is a critical factor for effective treatment of the disease and can increase the survival rate of BC patients. Long non-coding RNAs can act as miRNA decoys by sequestering miRNAs, thus acting as competing endogenous RNAs and leading to re-expression of miRNA target genes. Maternally expressed 3 (MEG3) is LncRNA and it was reported to be tumor suppressor in breast cancer. The study aims to investigate the effect of MEG3 SNP (rs7158663 G/A) and its association with breast cancer risk in the Egyptian population. In addition, demonstrate the consequence of the MEG3 polymorphism on the expression levels of MEG3, miR-182 and miRNA-29. MEG3 rs7158663 G /A was genotyped and serum MEG3, miRNA-182 and miRNA-29 were measured in 180 breast cancer, 120 FA, and 150 controls by the qPCR. Frequencies of MEG3 rs7158663 GA/AA genotype and A allele were significantly higher in BC patients compared to the controls results showed that serum MEG3 levels were significantly lower, according to the presence of the A allele in different study groups while the expression of miR-182 and miRNA 29 were significantly elevated. MEG3, miR-182 and miRNA-29 are key genes involved in the development of BC, are considered as a novel potential non-invasive diagnostic biomarker for BC.